Pendampingan Penerapan Sistem Informasi Desa Berbasis Web untuk Meningkatkan Tata Kelola Desa Digital di Desa Sunggal - Dybio Dompu Hot Asih; Dede Ardian Tarigan; Lestari Laia (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2026)
The development of information technology encourages village governments to improve the quality of digital governance and public services. However, Desa Sunggal still faces challenges in managing village administration manually, which leads to inefficiency and potential data management errors. This Community Service Program aims to assist in the implementation of a web-based village information system to enhance digital village governance in Desa Sunggal. The implementation methods include needs analysis, system design, development of a web-based village information system, training for village officials, and evaluation of system utilization. The developed system covers population data management, village administrative services, and digital document archiving. The results indicate that the implementation of the web-based village information system improves administrative efficiency, accelerates public service delivery, and enhances the digital competencies of village officials. Through this assistance program, Desa Sunggal is expected to achieve more transparent, effective, and sustainable village governance through the utilization of information technology.